Index to Proceedings of the Economic and Social Council 2023 - United Nations (United Nations, 2025)
The Index to Proceedings of the Economic and Social Council is a bibliographic guide to the proceedings and documentation of the Economic and Social Council. This issue covers the 2023 session of the Council including the organizational and substantive session. The Index is divided in two parts comprising the Subject Index and Index to Speeches. The Index is prepared by the Dag Hammarskjöld Library, Department of Global Communications, as one of the products of the United Nations Bibliographic Information System (UNBIS).